Ferritic stainless steel and method for producing same
By controlling the composition and annealing temperature of Nb, Si, Mn, Al in ferrite stainless steel, the problems of insufficient yield strength and poor oxidation resistance in the prior art are solved, and excellent yield strength and resistance at high temperatures are achieved. Oxidation, suitable for lightweight and durability improvement of automotive exhaust system components.
Patent Information
- Application Number
- CN202380043320.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-16
- Filing Date
- 2023-02-01
- Publication Date
- 2025-01-07
AI Technical Summary
The existing ferritic stainless steel has insufficient yield strength and poor oxidation resistance at high temperatures. Especially in thin-walled materials, it is easy to form oxides, resulting in reduced durability and clogging problems, making it difficult to meet the high-temperature use requirements of automobile exhaust system components.
By controlling the composition of the components, especially in the range of 1.10 to 3.00%, combined with 0.05 to 2.00% Si, 0.05 to 0.80% Mn, and 0.01 to 0.50% Al, the condition that the amount of solid solution Nb is greater than 1.00%. The final annealing treatment was carried out above 1120°C to prepare a ferrite stainless steel with excellent high temperature yield strength and oxidation resistance.
The 0.2% yield strength at 800°C is achieved above 60MPa, and the oxidation increase after 200 hours is maintained in an atmospheric atmosphere of 1000°C for 200 hours, which significantly improves the high-temperature performance and oxidation resistance of the material, and is suitable for automobiles. Lightweight and durability requirements for exhaust system components.
Smart Images

Figure CN119278289A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a ferritic stainless steel and a method for producing the same. In particular, the present invention relates to a ferritic stainless steel having excellent high temperature yield strength and excellent oxidation resistance suitable for use in exhaust system components used at high temperatures. Examples of exhaust system components used at high temperatures include exhaust pipes, exhaust manifolds, converter housings, and mufflers of automobiles and motorcycles (hereinafter also referred to as automobile exhaust pipes, etc.), and exhaust ducts of thermal power plants. Background Art
[0002] Exhaust system parts such as automobile exhaust pipes are required to have excellent high-temperature yield strength.
[0003] As a base material for such automobile exhaust system parts, ferritic stainless steel such as Type 429 (14 mass% Cr-0.9 mass% Si-0.4 mass% Nb system) in which Nb and Si are added in combination is often used.
[0004] In addition, SUS444 (19 mass% Cr-0.4 mass% Nb-2 mass% Mo) specified in JIS G4305 is being developed in which Nb and Mo are added in combination to improve the high temperature yield strength.
[0005] Furthermore, Patent Document 1 discloses: "A ferritic stainless steel sheet having excellent high temperature strength, characterized in that it contains, by mass%, C: 0.01% or less, N: 0.02% or less, Si: 0.05-1%, Mn: more than 0.6 and 2% or less, Cr: 15-30%, Mo: 1-4%, Cu: 1-3.5%, Nb: 0.2-1.5%, Ti: 0.05-0.5%, B: 0.0002-0.01%, and the remainder is composed of Fe and unavoidable impurities."
[0006] Patent Document 2 discloses: "A heat-resistant ferritic stainless steel sheet having excellent high temperature strength and weldability, comprising, by mass%, C: 0.02% or less, Si: less than 0.6%, Mn: 0.6% to 2.0%, S: 0.006% or less, P: 0.04% or less, Cr: 17.0% to 22.0%, Nb: more than 0.6% and less than 1.5%, Mo: 1.0% to 3.0%, V: 0.01% to 0. 5%, Cu: 0.1% or more and less than 0.3%, N: 0.02% or less, Al: 0.005% to 0.05%, O: 0.012% or less, wherein, within the above range, these elements are contained in a manner satisfying the relationship: C+N≤0.03%Mn / S≥20016.8≤0.6Cr+1.1Mo+8.2Nb≤24.0, and the remainder is composed of Fe and unavoidable impurities in manufacturing. "
[0007] In addition, as a ferritic stainless steel containing a large amount of W (hereinafter also referred to as W-containing ferritic stainless steel), for example, Patent Document 3 discloses "a ferritic stainless steel which is soft at room temperature and has excellent high temperature oxidation resistance, characterized in that it contains, by mass%, C: 0.02% or less, Si: 0.1% or less, Mn: 2.0% or less, Cr: 12.0 to 16.0%, Mo: 1.0 to 5.0%, W: greater than 2.0% and 5.0% or less, Nb: 5 (C + N) to 1.0% and N: 0.02% or less, and the remainder is a composition of Fe and unavoidable impurities."
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2009-215648
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 06-088168
[0012] Patent Document 3: Japanese Patent Application Publication No. 2004-018921 Summary of the invention
[0013] Regarding the high temperature yield strength, for example, if the 0.2% yield strength at 800°C is compared, Type 429 is about 30 MPa. In contrast, SUS444 is about 45 MPa, and the W-containing ferritic stainless steel disclosed in Patent Document 3 is about 52 MPa. That is, the yield strength of SUS444 and the W-containing ferritic stainless steel is about 1.5 to 1.7 times higher than that of Type 429. In addition, the high temperature yield strength of the ferritic stainless steel sheets disclosed in Patent Documents 1 and 2 is also at the same level as these.
[0014] However, in recent years, for example, from the viewpoint of reducing the weight of automobile bodies, there is a tendency to use thin-walled materials. In this case, a higher high-temperature yield strength than before is required.
[0015] In addition, oxidation resistance is also an important property for materials used in environments exposed to high-temperature exhaust gas, such as automobile exhaust system components. If the oxidation resistance is insufficient, a large amount of oxides will be generated during use. In particular, if a large amount of oxides are generated in thin-walled materials, the thickness will become insufficient during use, which will have an adverse effect on durability. In addition, oxides are easily peeled off, causing problems such as clogging in exhaust system components due to peeled oxides.
[0016] The present invention has been developed in view of the above-mentioned current situation, and an object of the present invention is to provide a ferritic stainless steel having significantly higher high temperature yield strength and excellent oxidation resistance than conventional ones.
[0017] Another object of the present invention is to provide a method for producing the above-mentioned ferritic stainless steel.
[0018] It should be noted that “excellent high temperature yield strength” means that the 0.2% yield strength at 800° C. is 60 MPa or more.
[0019] In addition, "excellent oxidation resistance" means that the oxidation increase after being kept at 1000°C in air atmosphere for 200 hours is 20 g / m 2 the following.
[0020] Here, the oxidation increment is calculated by the following formula.
[0021] [Oxidation increment (g / m 2 )] = [mass increase of the test piece before and after holding (g)] ÷ [surface area of the test piece (m 2 )]
[0022] Therefore, the inventors have repeatedly conducted intensive studies in order to achieve the above-mentioned object.
[0023] As a result, the following findings were obtained.
[0024] (A) By appropriately controlling the component composition, in particular, by containing Nb in the range of 1.10 to 3.00% and making the amount of solid-solution Nb greater than 1.00 mass%, the high-temperature yield strength is significantly improved compared with the conventional ones.
[0025] (B) By containing Si: 0.05 to 2.00%, Mn: 0.05 to 0.80%, and Al: 0.01 to 0.50% in the following ranges and satisfying the following formula (1), it is possible to significantly improve oxidation resistance while ensuring excellent high temperature yield strength.
[0026] (C) In order to ensure a predetermined amount of dissolved Nb, it is effective to prepare a to-be-treated material whose component composition is appropriately controlled as described above, and to subject the to-be-treated material to a final annealing treatment at a final annealing temperature of 1120° C. or higher.
[0027] The present invention has been completed through further research based on the above findings.
[0028] That is, the main configuration of the present invention is as follows.
[0029] [1] A ferritic stainless steel having the following composition:
[0030] In terms of mass%, C: 0.015% or less, Si: 0.05-2.00%, Mn: 0.05-0.80%, P: 0.040% or less, S: 0.010% or less, Al: 0.01-0.50%, N: 0.020% or less, Ni: 0.02-1.00%, Cr: 14.0-25.0%, Nb: 1.10-3.00% and Mo: 1.0-4.0%, the remainder being Fe and unavoidable impurities,
[0031] Satisfying the following relationship (1):
[0032] The amount of solid solution Nb is greater than 1.00% by mass.
[0033] [Si]-[Mn]>0.00···(1)
[0034] Here, [Si] and [Mn] are the Si and Mn contents (mass %) of the above-mentioned component composition, respectively.
[0035] [2] The ferritic stainless steel according to [1] above, wherein
[0036] The above-mentioned component composition further contains, in terms of mass%, one or more selected from the group consisting of Cu: 2.00% or less, V: 0.50% or less, W: 5.0% or less, Ti: 0.30% or less, REM: 0.50% or less, Zr: 0.50% or less, Co: 0.50% or less, B: 0.0050% or less, Ca: 0.0050% or less, Mg: 0.0050% or less, Sb: 0.50% or less, and Sn: 0.50% or less.
[0037] [3] A method for producing ferritic stainless steel, comprising the following steps:
[0038] A step of preparing a material to be processed having a component composition as described in [1] or [2] above, and
[0039] A step of subjecting the treated material to a final annealing treatment at a final annealing temperature of 1120° C. or higher.
[0040] According to the present invention, a ferritic stainless steel having a high temperature yield strength significantly superior to that of conventional ones, specifically, a high temperature yield strength of 60 MPa or more at 800°C, and excellent oxidation resistance can be obtained. Thus, in the ferritic stainless steel of the present invention, even if the thickness is reduced by about 50 to 30%, the same degree of yield strength can be obtained as compared with Type 429 (0.2% yield strength at 800°C: about 30 MPa) and SUS444 (0.2% yield strength at 800°C: 45 MPa). Therefore, the ferritic stainless steel of the present invention, by being applied to, for example, exhaust system components of automobiles, greatly contributes to the reduction of the weight of automobile bodies and the reduction of carbon dioxide emissions by improving fuel efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a schematic diagram of a test piece used for evaluating the high-temperature yield strength. DETAILED DESCRIPTION
[0042] The present invention will be described based on the following embodiments.
[0043] First, the component composition of the ferritic stainless steel according to one embodiment of the present invention will be described. It should be noted that the unit in the component composition is "mass %", and hereinafter, it is simply expressed as "%" unless otherwise specified.
[0044] C: 0.015% or less
[0045] C is an element effective in improving the strength of steel. However, if the C content is greater than 0.015%, toughness and formability decrease. In addition, C combines with Nb and precipitates as carbides. Therefore, as the C content increases, the amount of Nb carbide precipitation increases, and the amount of solid-dissolved Nb decreases. As a result, excellent high-temperature yield strength cannot be obtained. Therefore, the C content is set to 0.015% or less. From the viewpoint of ensuring formability, the C content is preferably 0.010% or less. The C content is more preferably 0.008% or less. In addition, from the viewpoint of ensuring strength as an exhaust system component of an automobile, the C content is preferably 0.003% or more. The C content is more preferably 0.004% or more.
[0046] Si: 0.05~2.00%
[0047] Si is an important element that improves oxidation resistance by promoting the formation of Cr2O3. In order to obtain this effect, the Si content is set to 0.05% or more. On the other hand, if the Si content is greater than 2.00%, the workability is reduced. In addition, Si promotes the precipitation of an intermetallic compound called Laves phase (hereinafter also referred to as Laves phase) composed of Fe2Nb. Therefore, if Si is excessive, the amount of dissolved Nb decreases, and excellent high temperature yield strength cannot be obtained. Therefore, the Si content is set to 2.00% or less. The Si content is preferably 1.00% or less. Furthermore, as described later, the Si content needs to be within the above range and within the range satisfying the formula (1) described later.
[0048] Mn: 0.05~0.80%
[0049] Mn is an element that acts as a deoxidizer and is also an element contained in order to increase the strength of steel. In order to obtain this effect, the Mn content is set to 0.05% or more. The Mn content is preferably set to 0.10% or more. However, excessive Mn content will lead to the formation of γ phase at high temperatures, which reduces oxidation resistance. Therefore, the Mn content is set to 0.80% or less. The Mn content is preferably set to 0.50% or less. Furthermore, as described later, the Mn content needs to be within the above range and within the range that satisfies the formula (1) described later.
[0050] P: 0.040% or less
[0051] P is a harmful element that reduces the toughness of steel. Therefore, P is preferably reduced as much as possible. Therefore, the P content is set to 0.040% or less. The P content is preferably 0.030% or less. It should be noted that the lower limit of the P content is not particularly limited. However, excessive P removal leads to an increase in cost, so the P content is preferably 0.005% or more.
[0052] S: 0.010% or less
[0053] S reduces elongation and r-value and has an adverse effect on formability. In addition, S is also a harmful element that reduces corrosion resistance, which is a basic characteristic of stainless steel. Therefore, S is preferably reduced as much as possible. Therefore, the S content is set to 0.010% or less. The S content is preferably 0.003% or less. It should be noted that there is no particular lower limit for the S content. However, excessive desulfurization leads to an increase in cost, so the S content is preferably 0.0005% or more.
[0054] Al: 0.01~0.50%
[0055] Al is an element that has the effect of improving oxidation resistance. In order to obtain this effect, the Al content is set to 0.01% or more. The Al content is preferably set to 0.05% or more. On the other hand, if the Al content is greater than 0.50%, the formation of Cr2O3 is hindered, and the oxidation resistance is reduced. Therefore, the Al content is set to 0.50% or less. The Al content is preferably set to 0.35% or less.
[0056] N: 0.020% or less
[0057] N is an element that reduces the toughness and formability of steel. In particular, if the N content is greater than 0.020%, the reduction in toughness and formability becomes significant. In addition, N combines with Nb and precipitates as nitrides. Therefore, as the N content increases, the amount of solid-dissolved Nb in the steel decreases, and excellent high-temperature yield strength cannot be obtained. Therefore, the N content is set to 0.020% or less. In addition, from the viewpoint of ensuring toughness and formability, N is preferably reduced as much as possible. Therefore, the N content is preferably less than 0.015%. It should be noted that the lower limit of the N content is not particularly limited. However, excessive denitrification leads to an increase in cost, so the N content is preferably 0.004% or more.
[0058] Ni: 0.02~1.00%
[0059] Ni is an element that improves the toughness of steel. In order to obtain this effect, the Ni content is set to 0.02% or more. The Ni content is preferably 0.05% or more. However, Ni is a strong γ phase forming element. Therefore, Ni generates γ phase at high temperatures to improve oxidation resistance. Therefore, the Ni content is set to 1.00% or less. The Ni content is preferably 0.50% or less.
[0060] Cr: 14.0~25.0%
[0061] Cr is an important element that is effective in improving the corrosion resistance and oxidation resistance that are the characteristics of stainless steel. In order to obtain this effect, especially sufficient oxidation resistance, the Cr content is set to 14.0% or more. The Cr content is preferably 18.0% or more. However, Cr is also an element that hardens and reduces the ductility of steel by solid solution strengthening of steel at room temperature. In particular, if the Cr content is greater than 25.0%, the hardening and reduction of ductility of the steel become significant. Therefore, the Cr content is set to 25.0% or less. The Cr content is preferably 20.0% or less.
[0062] Nb: 1.10~3.00%
[0063] As described later, in order to obtain the desired high temperature yield strength, it is necessary to make the amount of dissolved Nb greater than 1.00 mass%. Therefore, a treatment of dissolved Nb is performed, specifically, a final annealing treatment is performed under the condition of a final annealing temperature of 1120°C or above. However, even in this case, it may still be in the state of carbonitrides and intermetallic compounds, and insoluble Nb may be produced. Therefore, from the viewpoint of obtaining a specified amount of dissolved Nb, the Nb content is made to be 1.10% or more. The Nb content is preferably 1.60% or more. On the other hand, if the Nb content is greater than 3.00%, Laves phase is easily precipitated. As a result, for example, the toughness of the hot-rolled steel sheet is reduced, and the manufacturability is reduced. Therefore, the Nb content is made less than 3.00%. The Nb content is preferably less than 2.00%.
[0064] Mo: 1.0~4.0%
[0065] Mo is an element that dissolves in steel to increase the high temperature strength of steel, thereby increasing the high temperature yield strength. In order to obtain this effect, the Mo content is set to 1.0% or more. The Mo content is preferably 1.6% or more. However, if the Mo content is greater than 4.0%, the σ phase precipitates coarsely. Therefore, the toughness of the steel is greatly reduced. Therefore, the Mo content is set to 4.0% or less. The Mo content is preferably 3.0% or less.
[0066] [Si]-[Mn]>0.00···(1)
[0067] As described above, in a high-temperature oxidizing environment, Si promotes the formation of Cr2O3. In addition, Mn generates MnCr2O4. Compared with MnCr2O4, Cr2O3 is more dense and easier to peel off. Therefore, Cr2O3 has a higher effect on improving oxidation resistance. Therefore, in order to obtain excellent oxidation resistance, it is necessary to preferentially generate Cr2O3 rather than MnCr2O4. Here, which of MnCr2O4 and Cr2O3 is preferably generated depends on the relationship between the Si content and the Mn content. Specifically, in the case of Si-Mn>0.00, that is, when the Si content is greater than the Mn content, Cr2O3 is preferentially generated. On the other hand, in the case of Si-Mn≤0.00, that is, when the Si content is less than the Mn content, MnCr2O4 is preferentially generated. Therefore, from the perspective of obtaining excellent oxidation resistance, the key is to satisfy the above formula (1). Preferably, [Si]-[Mn]>0.05.
[0068] The basic component composition of the ferritic stainless steel according to one embodiment of the present invention has been described above. However, the component composition of the ferritic stainless steel according to one embodiment of the present invention may further contain at least one of the following optional additional elements alone or in combination.
[0069] Cu: 2.00% or less, V: 0.50% or less, W: 5.0% or less, Ti: 0.30% or less, REM: 0.50% or less, Zr: 0.50% or less, Co: 0.50% or less, B: 0.0050% or less, Ca: 0.0050% or less, Mg: 0.0050% or less, Sb: 0.50% or less, Sn: 0.50% or less Cu: 2.00% or less
[0070] Cu has the effect of greatly increasing the strength (yield strength) of steel by finely precipitating as ε-Cu at around 600°C. In order to obtain this effect, the Cu content is preferably 0.30% or more. The Cu content is more preferably 1.00% or more. On the other hand, if the Cu content is greater than 2.00%, the toughness is reduced. Therefore, when Cu is contained, the Cu content is set to 2.00% or less. The Cu content is preferably 1.80% or less.
[0071] V: 0.50% or less
[0072] V is an element effective in improving the workability of steel. In addition, by containing V, V combines with N in the steel and precipitates as fine nitrides. As a result, Nb is inhibited from combining with N to form nitrides. That is, V is an element that plays a beneficial role in ensuring the prescribed amount of solid-solution Nb and further increases the effect of improving high-temperature yield strength. In order to obtain this effect, the V content is preferably 0.01% or more. The V content is more preferably 0.03% or more. However, if the V content is greater than 0.50%, the toughness is reduced. Therefore, when V is contained, the V content is set to 0.50% or less. The V content is preferably 0.25% or less.
[0073] W: 5.0% or less
[0074] W is an element that improves the high temperature strength of steel by being dissolved in steel. In order to obtain this effect, the W content is preferably 0.1% or more. The W content is more preferably 1.0% or more. However, if the W content is greater than 5.0%, the surface properties will deteriorate. Therefore, when W is contained, the W content is 5.0% or less. The W content is preferably 3.5% or less.
[0075] Ti: 0.30% or less
[0076] Ti combines with C and N preferentially over Nb and precipitates as TiC or TiN. Therefore, Nb is inhibited from combining with N to form nitrides. That is, Ti is an element that plays a favorable role in ensuring the prescribed amount of solid-dissolved Nb and further increases the effect of improving high-temperature yield strength. In order to obtain this effect, the Ti content is preferably 0.01% or more. The Ti content is more preferably 0.03% or more. However, if the Ti content is greater than 0.30%, it leads to a decrease in toughness. Therefore, when Ti is contained, the Ti content is set to 0.30% or less. The Ti content is preferably 0.20% or less.
[0077] REM: 0.50% or less
[0078] REM (rare earth metals) refers to Sc, Y and lanthanide elements (elements with atomic numbers 57 to 71 such as La, Ce, Pr, Nd, and Sm). REM is an element that improves oxidation resistance. In order to obtain this effect, the REM content is preferably 0.01% or more. However, if the REM content exceeds 0.50%, the steel becomes brittle. Therefore, when REM is contained, the REM content is set to 0.50% or less.
[0079] Zr: 0.50% or less
[0080] Zr is an element that improves oxidation resistance. To achieve this effect, the Zr content is preferably 0.01% or more. However, if the Zr content is greater than 0.50%, Zr intermetallic compounds precipitate and embrittle the steel. Therefore, when Zr is contained, the Zr content is set to 0.50% or less.
[0081] Co: 0.50% or less
[0082] Co is an element effective in improving the toughness of steel. In order to obtain this effect, the Co content is preferably 0.01% or more. The Co content is more preferably 0.02% or more, and further preferably 0.03% or more. However, Co is an expensive element. In addition, if the Co content is greater than 0.50%, the above effect is saturated. Therefore, when Co is contained, the Co content is set to 0.50% or less. The Co content is preferably 0.20% or less, and more preferably 0.10% or less.
[0083] B: 0.0050% or less
[0084] B is an element effective in improving the workability of steel, especially the secondary workability. In order to obtain this effect, the B content is preferably 0.0002% or more. The B content is more preferably 0.0005% or more. On the other hand, if the B content is greater than 0.0050%, coarse BN is generated and the workability of the steel is reduced. Therefore, when B is contained, the B content is set to 0.0050% or less. The B content is preferably 0.0020% or less.
[0085] Ca: 0.0050% or less
[0086] Ca is an element effective in preventing nozzle clogging caused by the precipitation of inclusions that are easily generated during continuous casting. In order to obtain this effect, the Ca content is preferably 0.0002% or more. The Ca content is more preferably 0.0005% or more. On the other hand, in order to obtain good surface properties without generating surface defects, the Ca content is preferably 0.0050% or less. Therefore, in the case of containing Ca, the Ca content is 0.0050% or less. The Ca content is preferably 0.0030% or less, and more preferably 0.0020% or less.
[0087] Mg: 0.0050% or less
[0088] Mg is an element that increases the equiaxed crystal ratio of the slab, and improves workability and toughness. In addition, in steel containing Nb, Mg also has the effect of inhibiting the coarsening of Nb carbonitrides. In order to obtain these effects, the Mg content is preferably 0.0002% or more. The Mg content is more preferably 0.0004% or more. On the other hand, if the Mg content is greater than 0.0050%, the surface properties of the steel deteriorate. Therefore, when Mg is contained, the Mg content is set to 0.0050% or less. The Mg content is preferably 0.0030% or less, and more preferably 0.0020% or less.
[0089] Sb: 0.50% or less
[0090] Sb is an element that has the effect of improving the toughness of steel. In order to obtain this effect, the Sb content is preferably 0.01% or more. The Sb content is preferably 0.03% or more. On the other hand, if the Sb content is greater than 0.50%, the toughness of the steel decreases. Therefore, when Sb is contained, the Sb content is set to 0.50% or less. The Sb content is preferably 0.30% or less.
[0091] Sn: 0.50% or less
[0092] Sn is an element that has the effect of improving the corrosion resistance and high temperature strength of steel. In order to obtain this effect, the Sn content is preferably 0.01% or more. The Sn content is preferably 0.03% or more. On the other hand, if the Sn content is greater than 0.50%, the workability of the steel decreases. Therefore, when Sn is contained, the Sn content is set to 0.50% or less. The Sn content is preferably 0.30% or less.
[0093] The remainder other than the above elements is Fe and inevitable impurities. It should be noted that the above optional added elements may be 0%. In addition, when the content of each of V, W, Ti, REM, Zr, Co, B, Ca, Mg, Sb and Sn among the above optional added elements is less than the preferred lower limit, it can be said that the element is contained as an inevitable impurity.
[0094] Next, the steel structure of the ferritic stainless steel according to one embodiment of the present invention will be described.
[0095] The steel structure of the ferritic stainless steel according to one embodiment of the present invention has a ferrite phase with an area ratio of 97% or more. The ferrite phase may have an area ratio of 100%, that is, a ferrite single phase.
[0096] The area ratio of the remaining structure other than the ferrite phase is 3% or less. Examples of such a remaining structure include a martensite phase.
[0097] Here, the area ratio of the ferrite phase is calculated as follows.
[0098] A test piece for cross-sectional observation was made from stainless steel as a test material, and an etching treatment was performed using a saturated hydrochloric acid solution with picric acid. Next, 10 fields of view of the test piece were observed using an optical microscope at a magnification of 100 times, and the martensite phase and the ferrite phase were distinguished based on the structure shape. Next, the area ratio of the ferrite phase was obtained by image processing, and the average value was calculated to obtain the area ratio of the ferrite phase.
[0099] In addition, the area ratio of the remaining structure is obtained by subtracting the area ratio of the ferrite phase from 100%.
[0100] Furthermore, in the ferritic stainless steel according to one embodiment of the present invention, the key to forming the structure is a substantially ferrite single phase as described above, and the amount of solid solution Nb is greater than 1.00 mass %.
[0101] Solid solution Nb content: more than 1.00% by mass
[0102] Nb, in particular, effectively contributes to the improvement of high temperature yield strength by existing in a state of solid solution in steel. That is, if Nb is precipitated in the form of carbides, nitrides, and Laves phases such as NbC and NbN, the effect of improving high temperature yield strength will be reduced. Therefore, from the perspective of achieving the desired high temperature yield strength, the amount of solid solution Nb is made greater than 1.00 mass%. The amount of solid solution Nb is preferably 1.50 mass% or more. The upper limit of the amount of solid solution Nb is not particularly limited. The amount of solid solution Nb is, for example, preferably less than 2.50 mass%, more preferably less than 2.00 mass%. It should be noted that, as described later, in order to make the amount of solid solution Nb greater than 1.00 mass%, it is necessary to set the final annealing temperature to more than 1120°C. In addition, in order to make the amount of solid solution Nb more than 1.50 mass%, it is appropriate to set the final annealing temperature to more than 1200°C. It should be noted that the amount of solid solution Nb can be obtained by subtracting the amount of precipitated Nb from the Nb content (total Nb amount in steel) of the component composition. The details are described in the examples described later.
[0103] The shape of the ferritic stainless steel according to one embodiment of the present invention may be, for example, a plate shape (steel plate) or a tube shape (for example, a round tube or a square tube obtained by pipe-forming a steel plate).
[0104] Furthermore, the thickness of the ferritic stainless steel according to one embodiment of the present invention (plate thickness of the steel plate, wall thickness of the pipe) is not particularly limited, but is preferably 0.5 to 2.5 mm. In addition, the thickness of the ferritic stainless steel according to one embodiment of the present invention is more preferably 1.0 mm or more. The thickness of the ferritic stainless steel according to one embodiment of the present invention is more preferably 1.5 mm or less.
[0105] It should be noted that the characteristics (high temperature yield strength and oxidation resistance) of the ferritic stainless steel according to one embodiment of the present invention are as described above.
[0106] Next, a method for producing ferritic stainless steel according to one embodiment of the present invention will be described.
[0107] A method for producing ferritic stainless steel according to one embodiment of the present invention includes the following steps:
[0108] The step of preparing a material to be processed having the above-mentioned component composition, and
[0109] A step of subjecting the treated material to a final annealing treatment at a final annealing temperature of 1120° C. or higher.
[0110] Furthermore, a method for producing ferritic stainless steel according to an embodiment of the present invention is a method for producing the ferritic stainless steel according to an embodiment of the present invention described above.
[0111] It should be noted that, unless otherwise specified, the temperatures involved in the manufacturing method are based on the surface temperatures of the slab, hot-rolled steel plate, cold-rolled steel plate, processed material, etc.
[0112] [Preparation process]
[0113] First, a material to be processed (a blank to be subjected to a final annealing treatment described later) having the above-mentioned component composition is prepared. The method for preparing the material to be processed is not particularly limited.
[0114] For example, a known melting furnace such as a converter or an electric furnace is used to melt molten steel having the above-mentioned composition through any secondary refining, and a slab is made by continuous casting or ingot casting-blowing method. As secondary refining, ladle refining, vacuum refining, etc. can be cited, and the VOD method is particularly preferred. In addition, from the perspective of productivity and quality, the continuous casting method is preferred. Next, the slab is heated, and a cold-rolled steel sheet is obtained through various processes such as hot rolling, hot-rolled sheet annealing, and cold rolling according to conventional methods. In this way, a processed material having the above-mentioned composition can be prepared. It should be noted that cold rolling can be cold rolling once or twice or more with intermediate annealing. In addition, pickling can also be appropriately performed. In addition, hot-rolled sheet annealing can also be omitted. In addition, depending on the application, the hot-rolled steel sheet obtained after hot rolling can also be used as a processed material having the above-mentioned composition.
[0115] It should be noted that the conditions of each of the above steps can be in accordance with conventional methods, for example, preferably set to slab heating temperature: 1100-1250°C, the thickness of the hot-rolled steel sheet obtained after hot rolling: 3-6 mm, and the total reduction ratio of cold rolling: 50% or more (more preferably 60% or more, and further preferably 70% or more). The upper limit of the total reduction ratio of cold rolling is not particularly limited. For example, the total reduction ratio of cold rolling is preferably 90% or less.
[0116] [Final annealing process]
[0117] Next, it is important to perform a final annealing treatment on the treated material prepared as described above at a final annealing temperature of 1120° C. or higher. In this way, the ferritic stainless steel according to one embodiment of the present invention described above can be obtained.
[0118] Final annealing temperature: above 1120℃
[0119] In the final annealing treatment, Nb precipitated in the form of carbides, nitrides, and Laves phases (hereinafter also referred to as Laves phases) such as NbC and NbN is dissolved. The higher the final annealing temperature, the more Laves phases are dissolved, and the amount of dissolved Nb increases. Among them, in order to make the amount of dissolved Nb greater than 1.00 mass%, the final annealing temperature needs to be set to above 1120°C. The final annealing temperature is preferably above 1150°C, and more preferably above 1200°C. On the other hand, if the final annealing temperature is greater than 1250°C, the grains coarsen and the workability sometimes decreases. Therefore, the final annealing temperature is preferably below 1250°C. Here, the final annealing temperature is the highest temperature reached in the final annealing process. In addition, the final annealing time described later is the holding (retention) time in the temperature range of the final annealing temperature -10°C to the final annealing temperature. The temperature during holding may not always be constant. In addition, when a hot-rolled steel sheet is used as the material to be processed, hot-rolled sheet annealing can be used as the final annealing treatment, and the annealing temperature can be controlled within the above range.
[0120] In addition, when the final annealing time is less than 3 seconds, Laves phase is not fully dissolved, and it is sometimes difficult to make the dissolved Nb amount greater than 1.00 mass%. Therefore, the final annealing time is preferably more than 3 seconds. The final annealing time is more preferably more than 30 seconds. On the other hand, if the final annealing time is greater than 600 seconds, the grains are coarsened and the workability sometimes decreases. Therefore, the final annealing time is preferably less than 600 seconds. The final annealing time is more preferably less than 120 seconds.
[0121] The final annealing conditions other than those described above are not particularly limited and may be carried out according to a conventional method. In addition, the final annealing may be carried out by continuous annealing.
[0122] In addition, pickling may be appropriately performed after the above-mentioned final annealing treatment. In addition, brush grinding may be performed before pickling. Furthermore, skin pass rolling may be performed to adjust the shape, surface roughness and material of the steel plate according to the application.
[0123] The ferritic stainless steel thus obtained (for example, hot-rolled products such as hot-rolled steel sheets, cold-rolled products such as cold-rolled steel sheets) is then subjected to cutting, bending, stretching, drawing and other processing according to their respective uses, and is formed into parts. As parts, for example, exhaust pipes of automobiles, exhaust ducts of thermal power plants, and fuel cell-related parts (for example, separators, interconnectors, reformers) can be cited. The method for welding these parts is not particularly limited. For example, arc welding such as MIG (Metal Inert Gas), MAG (Metal Active Gas), TIG (Tungsten Inert Gas), spot welding, seam welding and other resistance welding, as well as high-frequency resistance welding such as resistance welding, high-frequency induction welding, etc. can be applied.
[0124] The production conditions other than those described above are not particularly limited and may be conventionally performed.
[0125] Example
[0126] Steel having the composition shown in Table 1 (the remainder is Fe and inevitable impurities) was melted and cast in a vacuum melting furnace to form a 50 kg steel ingot. Then, the steel ingot was heated to 1200°C and hot rolled to form a thin slab with a thickness of 35 mm. A thin slab with a length of 200 mm was cut from the thin slab. The cut thin slab was heated to 1150°C and then hot pressed to form a hot-rolled steel plate with a plate thickness of 5 mm. Then, the hot-rolled steel plate was annealed at a hot-rolled plate annealing temperature in the range of 1100 to 1250°C. Then, the hot-rolled steel plate (hereinafter also referred to as hot-rolled annealed plate) after hot-rolled plate annealing was ground. Then, the hot-rolled annealed plate was cold rolled with a reduction rate of 60% to prepare a cold-rolled steel plate with a plate thickness of 2.0 mm for the processed material (the billet for final annealing). Next, the prepared cold-rolled steel sheet is subjected to a final annealing treatment under the conditions shown in Table 1 to obtain ferritic stainless steel. Hereinafter, the cold-rolled steel sheet after the final annealing treatment is referred to as a cold-rolled annealed sheet. Here, the final annealing time is set to 15 seconds. In addition, the steel structure of the obtained ferritic stainless steel is identified by the above-mentioned method, and as a result, it is composed of a ferrite phase of more than 97% by area ratio. In addition, as a reference, SUS444 (No. 27), one of the steel types showing the highest heat resistance in the previous ferritic stainless steel, is made into a cold-rolled annealed sheet under the same conditions as above. Then, the determination of the amount of dissolved Nb described later and the evaluation of high temperature yield strength and oxidation resistance are carried out. It should be noted that the conditions not clearly stated are in accordance with conventional methods.
[0127] The amount of solid-solution Nb in the ferritic stainless steel thus obtained was measured in the following manner.
[0128] <Determination of the amount of dissolved Nb>
[0129] From the obtained ferritic stainless steel, a long strip of 10 mm in width and 50 mm in length was cut out, and the oxide film on all sides (six sides) of the long strip was removed by grinding. Next, the long strip was used for quantitative analysis of the precipitate. That is, using the electrolysis device made by Fujiwara Seisakusho: SPEED ANALYZER FV-128, the long strip was subjected to constant current electrolysis in 10 vol% acetylacetone-1 mass% tetramethylammonium chloride-methanol (hereinafter also referred to as 10% AA electrolyte) to extract the precipitate. The extraction residue was filtered using a membrane filter made of cellulose acetate (pore size: 0.2 μm, 47 mmφ). The collected extraction residue was placed in a platinum crucible together with the filter and incinerated at 580°C. Then, the incinerated extraction residue was melted with a gas burner after adding 0.75 g Na2O2 + 0.75 gLiBO4. Next, 25 ml of 0.8 mass% tartaric acid / 10 vol% sulfuric acid was added to dissolve the obtained molten product, and a solution was obtained which was fixed to 100 ml with pure water. Using this solution, the amount of Nb precipitated (the percentage of the mass of Nb precipitated relative to the mass of the long strip pieces) was analyzed by an ICP emission spectrometer. Then, the value obtained by subtracting the quantitative amount of Nb precipitated from the Nb content of the steel composition was used as the amount of solid solution Nb (mass %).
[0130] The obtained ferritic stainless steel was evaluated for (1) high temperature yield strength and (2) oxidation resistance according to the following test methods. The evaluation results are also shown in Table 1.
[0131] (1) High temperature yield strength
[0132] The obtained ferritic stainless steel is manufactured by machining Figure 1 The test piece was made into the shape shown in the figure. It should be noted that the parallel part is 60 mm. The prepared test piece was heated to 800°C and kept for 15 minutes before a tensile test was performed to measure the 0.2% yield strength (MPa). It should be noted that the tensile speed was 0.2 mm / min (deformation speed 5.6×10 -5 / s). Then, the high temperature yield strength was evaluated according to the following criteria.
[0133] Excellent (qualified, excellent): 80MPa or above
[0134] Good (qualified): 60MPa or more and less than 80MPa
[0135] Bad (unqualified): less than 60MPa
[0136] (2) Antioxidant properties
[0137] A test piece with a width of 20 mm and a length of 30 mm is made from the obtained ferritic stainless steel by machining. It should be noted that all surfaces (6 surfaces) of the test piece are polished with #320 sandpaper. Next, after degreasing the test piece with acetone, the size and mass of the test piece are measured. Next, the test piece is hung in an electric furnace set at 1000°C and kept in an atmospheric atmosphere for 200 hours for uniform heating. After holding, the furnace is cooled to room temperature. Next, the mass of the test piece is measured, and the oxidation increase is calculated by the following formula.
[0138] [Oxidation increment (g / m 2 )] = [mass increase of the test piece before and after holding (g)] ÷ [surface area (of all faces) of the test piece (m 2 )]
[0139] Then, the antioxidant properties were evaluated according to the following criteria.
[0140] Excellent (qualified, particularly excellent): oxidation increase is less than 10g / m 2
[0141] Good (qualified): oxidation increase is 10g / m 2 Above and less than 20g / m 2
[0142] Defective (unqualified): Oxidation increase 20g / m 2 above
[0143] It should be noted that, usually, if abnormal oxidation occurs, the oxidation increment is greater than 50 g / m 2 , but here it will be more stringent less than 20g / m 2 as a qualified benchmark.
[0144]
[0145] As shown in Table 1, in the examples of the invention, both excellent high temperature yield strength and excellent oxidation resistance were obtained. In addition, in the examples of the invention, the high temperature yield strength exceeded that of SUS444 (No. 27), a steel grade that exhibits the highest level of heat resistance among conventional ferritic stainless steels. The oxidation increment was also the same as or lower than that of SUS444.
[0146] On the other hand, in the comparative examples, at least one of the high-temperature yield strength and the oxidation resistance was insufficient.
[0147] That is, in No. 28, since Si exceeded the appropriate range, a sufficient amount of Nb dissolved in the solid solution could not be obtained, and the high temperature yield strength was unacceptable.
[0148] In No. 29, since Mn exceeded the appropriate range, the oxidation resistance was unacceptable.
[0149] In No. 30, since Al exceeded the appropriate range, the oxidation resistance was unacceptable.
[0150] In No. 31, since Ni exceeded the appropriate range, the oxidation resistance was unacceptable.
[0151] In No. 32, since Cr was below the appropriate range, the oxidation resistance was unacceptable.
[0152] In No. 33, since Nb was below the appropriate range, a sufficient amount of Nb dissolved in the solid solution could not be obtained, and the high temperature yield strength was unacceptable.
[0153] In No. 34, since Mo was below the appropriate range, the high temperature yield strength was unacceptable.
[0154] In No. 35, since Mo exceeded the appropriate range, the high temperature yield strength was unacceptable.
[0155] In No. 36, since [Si]-[Mn] was below the appropriate range, the oxidation resistance was unacceptable.
[0156] In No. 37, since the final annealing temperature was lower than the appropriate range, a sufficient amount of Nb dissolved in the solid solution could not be obtained, and the high temperature yield strength was unacceptable.
[0157] Industrial Applicability
[0158] The ferritic stainless steel according to one embodiment of the present invention is suitable for use as exhaust system components of automobiles, etc. In addition, the ferritic stainless steel according to one embodiment of the present invention can also be suitably used as exhaust system components of thermal power generation systems and solid oxide fuel cell-related components (separators, interconnectors, reformers, etc.).
Claims
1. A ferritic stainless steel having the following composition: In terms of mass%, C: 0.015% or less, Si: 0.05-2.00%, Mn: 0.05-0.80%, P: 0.040% or less, S: 0.010% or less, Al: 0.01-0.50%, N: 0.020% or less, Ni: 0.02-1.00%, Cr: 14.0-25.0%, Nb: 1.10-3.00% and Mo: 1.0-4.0%, the remainder being Fe and unavoidable impurities, Satisfying the following relationship (1): The amount of solid solution Nb is greater than 1.00% by mass. [Si]-[Mn]>0.00···(1) in, [Si] and [Mn] are the Si and Mn contents of the above-mentioned composition, respectively, expressed in mass %.
2. The ferritic stainless steel according to claim 1, wherein: The component composition further contains, in mass %, one or more selected from the group consisting of Cu: 2.00% or less, V: 0.50% or less, W: 5.0% or less, Ti: 0.30% or less, REM: 0.50% or less, Zr: 0.50% or less, Co: 0.50% or less, B: 0.0050% or less, Ca: 0.0050% or less, Mg: 0.0050% or less, Sb: 0.50% or less, and Sn: 0.50% or less.
3. A method for producing ferritic stainless steel, comprising the following steps: A process for preparing a material to be processed having a component composition as claimed in claim 1 or 2, and A step of subjecting the treated material to a final annealing treatment at a final annealing temperature of 1120° C. or higher.
Citation Information
Patent Citations
Heat resistant ferritic stainless steel sheet excellent in high temperature strength and weldability
JP1994088168A
Ferritic stainless steel soft at room temperature and excellent in high-temperature oxidation resistance
JP2004018921A
Ferritic stainless steel having excellent high temperature strength, and method for producing the same
JP2009215648A